STRUCTURAL EVALUATION ON PEDESTRIAN BRIDGE CONSTRUCTED OF TRUSS STRUCTURE AND CASTELLATED BEAM - Arief Panjaitan (Prodi Magister Teknik Sipil Unsyiah, 2022)
A pedestrian bridge is a structure linking a pedestrian or bike path over or around a major roadway, railway, or waterway. The truss bridge (TRB) and the bridge with a castellated beam (CBB) are the common models of the pedestrian bridge. Past studies have revealed the structural behavior of TRB and CBB, but the performances of both bridges have not yet been comparatively confirmed. This study examined the TRB and CBB structural performances to obtain the better bridge model due to applied loading. The research was started by establishing the bridge models and employing the load combinations. The analysis resulted in the internal forces and they were used to design the bridges. The design is referred to as the SNI-1729-2020. This research revealed that the TRB exhibited structural performances, i.e., deflection and internal force, better than those of the CBB. Nevertheless, due to the many steel members, the TRB presented a heavier bridge than the CBB.